2017
DOI: 10.1080/00071668.2016.1259531
|View full text |Cite
|
Sign up to set email alerts
|

Variations in endothelin receptor B subtype 2 (EDNRB2) coding sequences and mRNA expression levels in 4 Muscovy duck plumage colour phenotypes

Abstract: 1. Endothelin receptor B subtype 2 (EDNRB2) is a paralog of EDNRB, which encodes a 7-transmembrane G-protein coupled receptor. Previous studies reported that EDNRB was essential for melanoblast migration in mammals and ducks. 2. Muscovy ducks have different plumage colour phenotypes. Variations in EDNRB2 coding sequences (CDSs) and mRNA expression levels were investigated in 4 different Muscovy duck plumage colour phenotypes, including black, black mutant, silver and white head. 3. The EDNRB2 gene from Muscovy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…Whether the paternal A allele from Muscovy drakes also has an impact on white plumage coloration in its offspring remains to be elucidated. However, no similar SNPs and amino acid substitutions were found in EDNRB2 gene in domestic ducks (Anas platyrhynchos) and Muscovy drakes (Wu et al, 2017). These findings indicate that the EDNRB2 gene polymorphism that has associated with plumage colour in Muscovy drakes is completely different from domestic ducks (Li et al, 2015).…”
Section: Resultsmentioning
confidence: 75%
See 4 more Smart Citations
“…Whether the paternal A allele from Muscovy drakes also has an impact on white plumage coloration in its offspring remains to be elucidated. However, no similar SNPs and amino acid substitutions were found in EDNRB2 gene in domestic ducks (Anas platyrhynchos) and Muscovy drakes (Wu et al, 2017). These findings indicate that the EDNRB2 gene polymorphism that has associated with plumage colour in Muscovy drakes is completely different from domestic ducks (Li et al, 2015).…”
Section: Resultsmentioning
confidence: 75%
“…Over the past few years, only two studies have reported findings on the association between the polymorphism of EDNRB2 gene and plumage colour in duck species (Li et al, 2015;Wu et al, 2017). It has been reported that the domestic ducks (Anas platyrhynchos) from a cross between white Kaiya and the white Liancheng duck with spot phenotype displayed predominant AA genotype of c.995G>A SNP (Li et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations